2014
DOI: 10.1038/pr.2014.140
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for mechanisms of protection of supine sleep against sudden infant death syndrome: an integrated mechanism review

Abstract: Supine sleep decreases sudden infant death syndrome (SIDS) incidence, however the mechanisms for this are unclear. The triple risk model for SIDS requires that one or more underlying abnormalities of breathing or autonomic control are present; these are rare, but brainstem defects are found in most SIDS cases. Supine sleep increases sympathetic nervous system tone, and level of state organization, and may therefore act as a stressor. This is evidenced by physiological arousal, and by delayed neurodevelopment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 80 publications
3
10
0
1
Order By: Relevance
“…Our results showed that, of the four sleeping positions, the preterm infants remained in the supine position for a longer mean time, which was also the most frequent position. These findings were consistent with criteria in the international literature for preventing SIDS (Bergman, ; Horne, Bandopadhayay, et al., ). Global awareness campaigns have advocated the supine or side position as being the safest option, which has already contributed to a 50% reduction in mortality, as well as in the incidence of SIDS (Bergman, ; Horne, Bandopadhayay, et al., ; Sahni et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that, of the four sleeping positions, the preterm infants remained in the supine position for a longer mean time, which was also the most frequent position. These findings were consistent with criteria in the international literature for preventing SIDS (Bergman, ; Horne, Bandopadhayay, et al., ). Global awareness campaigns have advocated the supine or side position as being the safest option, which has already contributed to a 50% reduction in mortality, as well as in the incidence of SIDS (Bergman, ; Horne, Bandopadhayay, et al., ; Sahni et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Sudden infant death syndrome is associated with multiple serotonergic defects including serotonin deficiency and DMV abnormalities (1518, 62). We briefly review the vagal afferents, brainstem respiratory neurons, and the medullary serotonergic system.…”
Section: New Hypothesismentioning
confidence: 99%
“…The initial self-initiated gasp during such an event is dependent of optimal serotonin homeostasis in the brain, which is undermined in SIDS. Imbalance in serotonin homeostasis alters sleep rhythm, thus increasing the chances of AAE (15). …”
Section: Introductionmentioning
confidence: 99%
“…47 Sin embargo, hay otros niños que pueden ser vulnerables -por alteraciones genéticas en los neurotransmisores-, a los que no podemos identificar en la actualidad. 48 Cuando el recién nacido está en contacto piel a piel con su madre, puede estar en posición prona sobre el torso materno. En estas circunstancias, se debe cuidar que la cabeza del bebé esté girada hacia un lado con la nariz y la boca desobstruidas y con el cuello no flexionado.…”
Section: Conceptos Generalesunclassified